Exploring the Cultural Integration, Challenges, and Support Systems for Criminal Justice International Students at the University of Baguio - Moyao, Warren G.; Cayasfon, Karla G. (Technium Social Sciences Journal, 2025)
In today’s globalized world, universities continue to welcome students from diverse backgrounds, making it essential to understand the unique experiences of international students. This study dives into the experiences of three international students enrolled in the School of Criminal Justice and Public Safety at the University of Baguio during the 2024–2025 academic year. Through detailed, in-depth interviews, the research sheds light on their journey of cultural integration, the hurdles they face, and the support systems they rely on. One major challenge uncovered is the language barrier—many instructors use Tagalog and Ilocano during lessons, making it difficult for the students to fully grasp the material and participate actively. This barrier not only impacts their academic success but also contributes to feelings of isolation. Additionally, all three students identify as non-Christian and have encountered bullying and insensitivity related to their faith, exposing deeper issues of cultural and religious misunderstanding on campus. Academic adjustment is further complicated by fragmented class groupings, which leave students struggling to find a consistent peer community. The participants expressed a strong preference for more stable groupings to create connection and ease their adaptation. Support services like the international student center and library play important roles beyond academics, offering emotional refuge for students dealing with homesickness and loneliness. However, not all students are equally aware of these resources, pointing to communication gaps that need attention. Overall, this study highlights how embracing cultural diversity enriches campus life and calls for practical steps—such as language accommodation, better communication, and cultural sensitivity training—to help international students succeed and feel truly included.